Evidence supportive of a bacterial component in the etiology for Alzheimer’s disease and for a temporal-spatial development of a pathogenic microbiome in the brain - Moné, Yves; Earl, Joshua P.; Król, Jarosław E.; Ahmed, Azad; Sen, Bhaswati; Ehrlich, Garth D.; Lapides, Jeffrey R. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Over the last few decades, a growing body of evidence has suggested a role for various infectious agents in Alzheimer’s disease (AD) pathogenesis. Despite diverse pathogens (virus, bacteria, fungi) being detected in AD subjects’ brains, research has focused on individual pathogens and only a few studies investigated the hypothesis of a bacterial brain microbiome. We profiled the bacterial communities present in non-demented controls and AD subjects’ brains. Results We obtained postmortem samples from the brains of 32 individual subjects, comprising 16 AD and 16 control age-matched subjects with a total of 130 samples from the frontal and temporal lobes and the entorhinal cortex. We used full-length 16S rRNA gene amplification with Pacific Biosciences sequencing technology to identify bacteria. We detected bacteria in the brains of both cohorts with the principal bacteria comprising Cutibacterium acnes (formerly Propionibacterium acnes) and two species each of Acinetobacter and Comamonas genera. We used a hierarchical Bayesian method to detect differences in relative abundance among AD and control groups. Because of large abundance variances, we also employed a new analysis approach based on the Latent Dirichlet Allocation algorithm, used in computational linguistics. This allowed us to identify five sample classes, each revealing a different microbiota. Assuming that samples represented infections that began at different times, we ordered these classes in time, finding that the last class exclusively explained the existence or non-existence of AD. Conclusions The AD-related pathogenicity of the brain microbiome seems to be based on a complex polymicrobial dynamic. The time ordering revealed a rise and fall of the abundance of C. acnes with pathogenicity occurring for an off-peak abundance level in association with at least one other bacterium from a set of genera that included Methylobacterium, Bacillus, Caulobacter, Delftia, and Variovorax. C. acnes may also be involved with outcompeting the Comamonas species, which were strongly associated with non-demented brain microbiota, whose early destruction could be the first stage of disease. Our results are also consistent with a leaky blood–brain barrier or lymphatic network that allows bacteria, viruses, fungi, or other pathogens to enter the brain.